Pedagogical Technologies in Teaching Students About Web Programming - Abrorjon Kholmatov (Zien Journals, 2023)
The rapid evolution of web technologies in recent years has underscored the importance of equipping students with the knowledge and skills necessary to excel in the field of web programming. This abstract provides an overview of the pedagogical technologies and innovative approaches that educators can employ to effectively teach students about web programming. Traditional methods of teaching web programming often struggle to keep pace with the constantly evolving landscape of web development. To address this challenge, this abstract explores the integration of modern pedagogical technologies that can enhance the learning experience for students.
Keywords: Pedagogical technologies; Teaching methods; Web programming